Modeling and analysis of solar-powered electric vehicles - Mandakuriti Nivas; Rambilli Krishna Prasad Rao Naidu; Debani Prasad Mishra; Surender Reddy Salkuti (Institute of Advanced Engineering and Science, 2022)
The emission of greenhouse gasses from transportation vehicles is one of the most alarming environmental threats and the emission of these gases is mounting at a distressing pace. Limited fossil fuel resources are also a threat to the automobile industry. This work aims to describe the solar-powered electric vehicle (SPEV) as the key to solving the downside of fuel and pollution. A battery is used in an electric vehicle (EV) which is charged from both external power supply and also from photovoltaic (PV) panels which absorb radiation from the sunlight and generate electrical power. A maximum power point tracker (MPPT) controller is employed to track the utmost power. A buck-Boost converter is utilized to amplify the DC voltage procured from the photovoltaic module and then the boosted output is transmitted to a three-phase voltage source inverter (VSI). VSI is used to transform the solar DC voltage to AC voltage and feeds the brushless direct current (BLDC) motor which controls vehicle applications.